A Bird Eye View on Recent Developments of Community Health Providers in India - M. Nirapure, Jyoti (International Journal of Nursing Research, 2023)
In this research work discuss a recent development in the area of community health providers (CHP). In the last few years, India face many challenges in community health services sector. Recent India move on giant development in the area of CHPs. For any development and changes required a legal amendment, for development of community health national medical commission bill presented the midlevel medical practitioner under chapter V (autonomous board), clause no-32. In the research work also discuss the previous work presented in area of CHPs in India. In short discuss the role of community health officers in India for the improvement of health services. Although being the backbone of the COVID-19 campaign in India, community health workers’ welfare but also employment conditions have not received enough attention. The nationwide lockdown, which was announced in March 2020, caused a migration of migratory workers from cities to home villages and towns, placing a heavy burden on public services and public health professionals. Regular immunizations, childcare services, and education suffered as a result of staff in these fields being redirected to cope with the containment of COVID-19 and especially those working in rural India. Field Epidemiology Training Program, strengthens the capacity of the public health workforce to detect, respond, and control disease outbreaks at the source. CDC India continues to support advanced, intermediate and frontline FETP programs, provide mentorship for outbreak investigations, surveillance evaluations, COVID-19 activities, and regular remote training. This research work also focuses on other major issues and problem of CHPs. Not only in COVID time duration but also after pandemics.